Optimal Economic Dispatch of Thermal-Wind Power Systems with Valve-Point Effects using A Modified JAYA Algorithm (The International Journal of Engineering & Information Technology (IJEIT), 2024)
In this paper, a modified JAYA algorithm isapplied to solve the optimization problem of the economic load dispatch (ED). The valve-point effects as well as thesystem power losses are taken into account in the solution.The optimization problem is formulated to include windpower within the generation system. The consideration ofwind power is motivated by the globally increasing interestin the renewable energy sources in light of theenvironmental aspects. The JAYA algorithm is a recentlyintroduced optimization technique which has beenemployed to solve small-scaled optimization problems.Nevertheless, the algorithm’s convergence behaviour hasnot shown satisfying characteristics for large scaleconstrained optimization problems. To overcome thedrawbacks associated with the complex nonlinearities andhigh dimensionalities, some enhancements to thealgorithm’s features are embedded. The proposed algorithmis validated using some well-known test systems. Acomparison of the results with other algorithms is carriedout considering the effects of valve point as well as power losses.